2017
DOI: 10.1177/2192568217708777
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Insufficiency as a Predictor for Adverse Outcomes in Adult Spinal Deformity Surgery

Abstract: Study Design:Retrospective analysis of prospectively collected data.Objective:The effect of malnutrition on outcomes after general surgery has been well reported in the literature. However, there is a paucity of data on the effect of malnutrition on postoperative complications during adult deformity surgery. The study attempts to explore and quantify the association between hypoalbuminemia and postoperative complications.Methods:A retrospective cohort analysis was performed on the American College of Surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
3
21
1
Order By: Relevance
“…3,012 articles underwent title and abstract screening and 31 studies were selected for full-text review. 18 studies were excluded with reasons and 13 were included in the review (10)(11)(12)(13)(14)(15)(18)(19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…3,012 articles underwent title and abstract screening and 31 studies were selected for full-text review. 18 studies were excluded with reasons and 13 were included in the review (10)(11)(12)(13)(14)(15)(18)(19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…12 In a study on adult lumbar deformity surgeries using the National Surgical Quality Improvement Program (NSQIP) database, hypoalbuminemia showed to be a risk factor for mortality, increased length of stay, any complications, and 30-day mortality. 13 On the other hand, a single institution study demonstrated that a low preoperative albumin level may be a risk factor for surgical site infections (SSI) in spine surgeries overall, but it was not seen to be statistically significant. 14 Additionally, a retrospective analysis of patients undergoing PLIF in the NSQIP database did not find low serum albumin to be a significant predictor of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, while past literature has identified patients at risk for extended LOS, there is little research on determinants of short LOS after ASD surgery. Given that most studies have defined extended LOS as either >75th percentile or an arbitrary value of greater than 5 days, [15][16][17][18] historically identified factors may not be applicable to the creation of expedited care pathways. Furthermore, very few studies have reported on the relationship between LOS and process components of the hospital course, such as mobilization protocols or the intraoperative details of surgery (such as blood loss, length of surgery, or levels of fusion), modifiable factors that show promise in reducing LOS.…”
Section: Introductionmentioning
confidence: 99%